CONCEPTUAL STRUCTURE OF “COURAGE”: CORE MEANING, PERIPHERAL MEANINGS, AND EMOTIONAL-EVALUATIVE COMPONENTS - M.K. Juraeva (International Journal of Literature and Language Studies, 2026)
Abstract: This article examines the conceptual structure of “courage” from cognitive and semantic perspectives. Courage is considered one of the central moral-spiritual concepts represented in language and culture. The study investigates the prototype meaning of courage, its peripheral semantic extensions, and its emotional-evaluative components. Using cognitive linguistics, semantic field theory, and discourse analysis, the research explores how courage is conceptualized and verbalized in language. The findings reveal that courage consists of a stable conceptual core associated with bravery and resistance to fear, while peripheral meanings include persistence, sacrifice, leadership, and moral responsibility. Emotional and evaluative components further enrich the concept by linking courage with positive social and cultural values. The study contributes to understanding the organization of moral concepts within the semantic field of spirituality.